Martin Luther se leer oor die doop volgens sy De Captivitate Babylonica Ecclesiae praeludium van 1520 - Pont, A. D. (Hervormde teologiese studies, 1998)
Martin Luther's doctrine of baptism according to the De captivitate Babylonica ecclesiae praeludium of 1520. In this study Luther's doctrine on baptism, as found in his 'De captivitate Babylonica ecclesiae praeludium' of 1520 is studied. This is not an exhaustive study of Luther's complete doctrine on baptism. It only explores his views on this sacrament which, according to his thesis, is held in captivity by the Roman doctrine on baptism. It is found that Luther, in this work, shifts the existing emphasis on the sacramental elements to the primacy of the Word and faith in that redemptive Word.